2021
DOI: 10.1111/1744-9987.13773
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hemodialysis patient with critical COVID‐19

Abstract: Introduction:The clinical course of hemodialysis patients with COVID-19 still remains unclear.Methods: Thirty-four hemodialysis patients were retrospectively enrolled. Patients were divided according to disease severity, and clinical symptoms and laboratory data at admission were compared. Results:The serum C-reactive protein (CRP) level, D-dimer level, and white blood cell (WBC) count were significantly higher in the group with critical disease than in the group with mild to severe disease (p = 0.005, p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, these patients also show impaired antiviral immune responses because of their impaired kidney functions. Hemodialysis patients with COVID-19 reportedly have a poor prognosis [5][6][7][8][9]. In the present study, we examined the clinical characteristics of hemodialysis patients with COVID-19 during the 6th wave of infection at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these patients also show impaired antiviral immune responses because of their impaired kidney functions. Hemodialysis patients with COVID-19 reportedly have a poor prognosis [5][6][7][8][9]. In the present study, we examined the clinical characteristics of hemodialysis patients with COVID-19 during the 6th wave of infection at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis patients must continue to receive lifesustaining treatment, typically three times per week, while hemodialysis attendance via travel to and from the center entails a close interaction with possible SARS-CoV-2 infected individuals [29,30]. In addition, hemodialysis patients have multiple risk factors for severe COVID-19, as several studies have reported a significantly increased risk of transmission of infection with COVID-19 and a higher mortality rate in hemodialysis patients compared with the general population [8,[31][32][33][34]. In a single center study from Italy among 55 hemodialysis patients infected with COVID-19, the authors reported a mortality rate of 52.0% [31], while data from 25 hemodialysis patients hospitalized with COVID-19 in Turkey revealed that COVID-19 disease has a significantly more severe course and worse prognosis with a mortality rate of 20% in hemodialysis patients [32].…”
Section: Discussionmentioning
confidence: 99%